Effects of cation types on physicochemical parameters and micro-structure of soft clay for electrochemical treatment - Guohui Yuan; Xiaomeng Cao; Ziyang Gao; Junfeng Ni; Xiaobing Li; Hongtao Fu; Jianqi Wu; Chenyang Zhou (Scientific Reports)
Abstract To investigate the influence of cations on the microstructural characteristics of electrochemical reinforcement in soft clay, a study was conducted using three different cationic salt solutions—NaCl, CaCl₂, and FeCl₃—for grouting treatment. Four sets of indoor experiments were performed to examine the reinforcement mechanism of the electrochemical method. The findings indicate that increasing the valence of injected cations significantly affects the electrochemical reinforcement effect and the soil’s microstructural properties. Higher-valence cations notably enhanced the soil’s electrical permeability coefficient and conductivity, leading to a substantial improvement in shear strength. Furthermore, the pore volume of the soil increased following electrochemical treatment compared to soil treated solely by electro-osmosis, due to the flocculation effect induced by cation injection. Nevertheless, the pore size distribution became more uniform, especially in the cathode region, as a result of pore redistribution. The chemical cementation reactions triggered by Ca2+ and Fe3+ injections mitigated the impact of flocculation on the microstructure, resulting in a more favorable pore volume and size distribution compared to Na+ treatment.